Efficiency Assessment on Codified Knowledge Products: An SFA Approach - Ferro, Gustavo Adolfo (2024)
Knowledge applied to innovation is increasingly recognized as an explanatory factor of economic growth. Innovation derives from applying knowledge to generate new products or processes. National Innovation Systems (NIS) performs as the formal or informal network of people within institutions, interacting to produce and apply knowledge to innovation. NIS can be understood as two subsystems: one based on scientifical and technological work, producing codified products (publications and patents), and the other centered on practical actions to diffuse, apply, and use knowledge. Our objective is to assess cost efficiency in the production of codified knowledge outputs (CKO), being our unit of analysis NIS (countries). To attain our goal, we apply a Stochastic Frontier Analysis (SFA) to estimate a cost frontier of CKO. The sample is a panel that includes 1189 observations, for 23 years (1996-2019), and 82 countries. Our main results identify determinants and patterns of efficiency and productivity, tendencies, and specifics of countries and groups of them.